Soil clay minerals abundance mapping using AVIRIS-NG data - Priya, Swati; Ghosh, Ranendu (Advances in space research, 2024)
Advanced hyperspectral remote sensing technology can identify various clay minerals in the soil. The improved spectral and spatial resolution of the airborne hyperspectral sensor can be used for a better interpretation of clay mineral abundance in the soil. This research utilizes the high-resolution image data acquired from Advanced Visible Infrared Imaging Spectrometer Next Generation (AVIRIS-NG) on an airborne platform to map the abundance of clay minerals in the Udaipur region of Rajasthan (24° 34′ 16.5720′' N, 73° 41′ 29.5584′' E). The representative soil samples for various soil clay minerals, e.g., kaolinite, montmorillonite, and illite, were classified from AVIRIS-NG data using a spectral feature fitting algorithm. A total of thirty sites were selected from agricultural and wastelands for soil sample collection. X-ray diffraction (XRD) analysis of representative soil samples was carried out to find the percentage and type of clay minerals present. Regression analysis between absorption peak depth values estimated from the hyperspectral image of the sampling sites in the spectral region from 2205 to 2214 nm and corresponding clay content value showed a significant relationship. The regression line obtained for the known pixels was used to prepare the mineral abundance map over the study area. This study significantly indicates the dominance of montmorillonite clay mineral over kaolinite and illite in the soils of the Udaipur region.